The big five in context: personality, diversity and attitudes toward equal opportunities for immigrants in Switzerland - Ackermann, Kathrin; Ackermann, Maya (Swiss political science review, 2015)
The paper analyzes the link between personality traits and attitudes of Swiss citizens toward equal opportunities for immigrants. In particular, we examine the extent to which this relationship is moderated by the socio-structural context. We test the assumption that the direct links between personality traits and attitudes toward equal opportunities are strengthened by perceived ethnic diversity. Based on our empirical analyses, we are able to replicate central findings of the research on personality traits and attitudes toward immigrants for the Swiss context. While openness toward experience and agreeableness are positively related to a preference for equal opportunities, conscientiousness is negatively linked to these attitudes. Furthermore, our results reveal that the link between conscientiousness and attitudes toward equal opportunities is significantly moderated by the perceived share of foreigners in the neighborhood. This finding is especially relevant for future research on the effects of personality traits.
Gesehen am 14.04.2021